Tlr2 on Bone Marrow and Non-Bone Marrow Derived Cells Regulates Inflammation and Organ Injury in Cooperation with Tlr4 During Resuscitated Hemorrhagic Shock. Issue 5 (November 2016) - Korff, Sebastian; Loughran, Patricia; Cai, Changchun; Fan, Jie; Elson, Greg; Shang, Limin; Pires, Susana Salgado; Lee, Yi Shan; Guardado, Jesse; Scott, Melanie; Billiar, Timothy R.
ABSTRACT: Background: Although the role of TLR4 in driving inflammation and organ injury after hemorrhagic shock and resuscitation (H/R) is well established, the role of TLR2—another receptor for damage-associated molecular pattern (DAMP) molecules—is not. In this study, we used a combination of TLR2 −/− and wild type (WT) mice treated with anti-TLR2 and anti-TLR4 neutralizing monoclonal antibodies (mAb) to discern the contribution of TLR2 relative to TLR4 to the systemic inflammatory response in murine H/R. Material and Methods: WT mice, TLR2 −/−, and WT mice receiving an anti-TLR2 or an anti-TLR4 mAB (given as a pretreatment) were sacrificed at 6 or 20 h post-H/R. Bone marrow TLR2/WT chimeric mice were created to assess the importance of immune and nonimmune cell-associated TLR2. Results: TLR2 −/− mice subjected to H/R exhibited significantly less liver damage and lower markers of systemic inflammation only at 20 h. Bone marrow chimeric mice using combinations of TLR2 −/− mice and WT mice demonstrated that TLR2 on non-bone marrow derived cells played a dominant role in the differences at 20 h. Interestingly, WT mice treated with anti-TLR2 mAB demonstrated a reduction in organ damage and systemic inflammation at both 6 and 20 h following H/R. A combination of anti-TLR2 mAB and anti-TLR4 mAB showed that both receptors drive IP-10 and KC levels and that there is cooperation for increases in IL-6, MIG, and MCP-1 levels between TLR2 and TLR4. Conclusion: These data also support the conclusion that TLR2 and TLR4 act in concert as important receptors in the host immune response to H/R.